2015
DOI: 10.5130/ccs.v7i1.4245
|View full text |Cite
|
Sign up to set email alerts
|

Working across Cultural Spheres: The Knowledge Sharing Practices of Boundary spanners in a Global Insurance Firm

Abstract: As organisations are becoming increasingly complex from a cultural perspective, it is important to understand how practitioners manage the differences that arise when working with peers that engage in different cultural (national cultural, professional, functional) spheres. The purpose of this paper is to contribute to practice-based research on knowledge sharing by using a discourse analytic lens which exposes the link between the knowledge (sharing) practices of boundary spanners at cultural interfaces and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 38 publications
(33 reference statements)
0
1
0
Order By: Relevance
“…Objects mediate knowledge transformation in social contexts, so their use can be influenced by the competing interests of the actors involved (Carlile, 2004;Heizmann, 2015) though how power influences knowledge practices is not yet fully understood (Hislop, 2013). In an examination of knowledge transformation across professional boundaries, Kimble, Grenier and Goglio-Primard (2010) reported that while the choice of boundary objects was usually made on the basis of complexity of the innovation involved, in a significant number of cases, those choices were also made on a political basis, by actors in positions of authority on the basis of their own interests.…”
Section: Knowledge 'Flow'mentioning
confidence: 99%
“…Objects mediate knowledge transformation in social contexts, so their use can be influenced by the competing interests of the actors involved (Carlile, 2004;Heizmann, 2015) though how power influences knowledge practices is not yet fully understood (Hislop, 2013). In an examination of knowledge transformation across professional boundaries, Kimble, Grenier and Goglio-Primard (2010) reported that while the choice of boundary objects was usually made on the basis of complexity of the innovation involved, in a significant number of cases, those choices were also made on a political basis, by actors in positions of authority on the basis of their own interests.…”
Section: Knowledge 'Flow'mentioning
confidence: 99%